The Impact of Social Media Usage On Students’ Academic Performance (SAP) - Sutarno, Sutarno (STKIP Muhammadiyah Pringsewu, 2019)
This study investigated to what extended do students used social media related to academic purposes and its impact on students? academic performance. This study applied a qualitative research method through using of social media and academic performance of students? questionnaire (SMAAPOS) adapted from Osharive (2015). The result showed that social media could be used as means of communication among students, and students to lecturer. The students also used the social media to get better understanding on the course taken. Then, the social media usage has impacted the students? academic performance positively. Keywords: Social Media Usage, Students Academic Performance (SAP), Impact.